The Effectiveness of Digital Virtual Reality-Based Therapy in Reducing Anxiety Among Patients Undergoing Gastrointestinal Endoscopy - Bayu Aji Sismanto; Dewi Gayatri; Dhea Natashia; Wati Jumaiyah; Winda Yuniarsih (Universitas Pahlawan Tuanku Tambusai, 2025)
Psychological responses such as anxiety often arise from negative perceptions in situations perceived as threatening, even when they should not induce fear. These anxiety-induced responses can lead to increased hemodynamic parameters such as elevated blood pressure, heart rate, and respiratory rate—particularly prior to medical procedures. This study aimed to evaluate the effectiveness of a digital virtual reality (VR)-based therapeutic intervention in reducing patient anxiety before undergoing gastrointestinal endoscopy. A quasi-experimental design was employed, involving both an experimental group and a control group using a pretest-posttest control group approach. Anxiety levels were measured using the State-Trait Anxiety Inventory (STAI). The intervention consisted of a 6-minute immersive VR video featuring calming mountain and beach scenery. A total of 50 respondents participated, with 25 in each group. Data were analyzed using paired and independent t-tests. Results showed no statistically significant difference in mean anxiety scores between the intervention and control groups (MD = 0.23, df = 48, t = 0.59, 95% CI: -0.56 to 1.03, p > 0.001). These findings suggest that the digital VR-based therapy was not statistically effective in reducing pre-endoscopy anxiety. Future interventions may require more immersive and interactive VR experiences—such as 360-degree simulations of endoscopic procedures—to achieve more substantial effects.